Hemodynamic Analyses of Different Stent Strut Configurations in the Carotid Artery - Ahmad Faiz Mat Zin; Taib, Ishkrizat; Muhammad Affiq Syukri Arafat; Nur Amani Hanis Roseman; Muhammad Afiq Mohd Nazri; Muhammad Afif Rifaie Aziz; Muhamad Zaqwan Az-Zikry Norzaidey; Muhammad Sufi Roslan; Takahisa Yamamoto; Awaludin Martin; Mohd Zainizam Mazlan (International Journal of Integrated Engineering, 2025)
Vascular stents are essential for treating blockages in the carotid artery, as they restore blood flow and diminish the risk of strokes. However, stents with poor strut configuration can disrupt normal blood flow, leading to turbulence and vortex formation, which may result in low shear stress and an increased potential for clot formation. This study explores the hemodynamic effects of three stent designs with distinct hemodynamic profiles: Type 1 (rectangular struts), Type 2 (hybrid cells), and Type 3 (helical pattern). This study examines the effectiveness of specific stent designs in reducing flow disturbances within a Y-shaped carotid artery model, focusing on three critical locations: the proximal inlet, just before bifurcation, and the distal segment of one daughter branch. In this study, the blood was modeled as a non-Newtonian fluid governed by a Carreau-Yasuda viscosity model using ANSYS. Key parameters included an inlet velocity of 0.5 m/s, infinite shear viscosity of 0.0035 Pa·s, and zero shear viscosity of 0.056 Pa·s. The findings indicate that both stent mesh configuration and implantation location significantly influence local flow dynamics that lead to increased recirculation and eddy formation near the bifurcation, while others facilitated smoother flow, thereby decreasing the risk of thrombosis. Type 3 demonstrated superior hemodynamic performance with balanced wall shear stress (WSS) distribution (peak WSS = 3.025 Pa) and minimal flow disruption, suggesting its potential to reduce thrombosis risk compared to Type 1 and 2 designs. This study highlights the importance of integrating advanced stent designs with anatomically informed placement to enhance flow dynamics and minimise thrombus formation.